Boosting of Cellular Immunity against Mycobacterium tuberculosis and Modulation of Skin Cytokine Responses in Healthy Human Volunteers by Mycobacterium bovis BCG Substrain Moreau Rio de Janeiro Oral Vaccine - Cosgrove, Catherine A. (American Society for Microbiology, 2006)
Oral immunization of healthy adults with 10(7) CFU BCG Moreau Rio de Janeiro was well tolerated and significantly boosted gamma interferon responses to purified protein derivative, Ag85, and MPB70 from previous childhood intradermal BCG immunization. Oral BCG offers the possibility of a needle-free tuberculosis vaccine and of boosting the protective immunity from intradermal tuberculosis vaccines.